A rare cause of scrotal abscess: xanthogranulomatous epididymitis - Panchal, Brinda B.; Thakore, Digpal H.; Tiwari, Pawan; Godara, Navyam; Kataria, Doyel (International Surgery Journal, 2022)
Xanthogranulomatous epididymitis is a rare benign process with destruction of tissue and replacement by cellular infiltration of foamy macrophages, dense lymphocytes and plasma cells. Literature has very few case reports. We reported here a case of a 72 years old male who presented as scrotal abscess with bilateral hydrocele on ultrasound. On exploration he had normal right testis with abscess localized to epididymis underwent right epididymectomy with orchidopexy. Histopathology reported necrosis and abundant foamy macrophages and plasma cells findings suggestive of xanthogranulomatous epididymitis.